A description of full blood count abnormalities in HIV-infected children less than three years of age before and after combined antiretroviral therapy initiation - Mabaso, Theodore Mlungisi (My University, 2016)
Background: Early cART reduces mortality and morbidity in HIV-infected children. Cytopaenias may develop in HIV-infected individuals, contributing to poor outcomes and few descriptions of cytopenias are available in children. Objectives: Describe the prevalence and outcomes of cytopaenias at baseline (cART initiation) and 6 and 12 months in HIV-infected children at Chris Hani Baragwanath Academic Hospital. Methods: Electronic and paper-based records of HIV-infected children under 3 years of age and initiating cART between the 1st January 2010 and 31st December 2012 were reviewed. Anthropometric measurements, clinical characteristics and laboratory findings at baseline, 6 and 12 months of cART were collected for analysis and compared at each outcome. Results: At baseline, the 185 HIV-infected children eligible for this study had a median age of 13 months (range 1 – 36), with advanced disease: 44% were underweight and stunted, 31% were wasted; 92% had WHO stage III/IV, CD4 count <15% in 36% and 85.5 % had a viral load ≥100 000 copies/ml. The median haemoglobin was 9.9 g/dl, white cell count 11.8 x 109/L and platelet count 354 x 109. Anaemia, thrombocytopaenia and leukopaenia were present in 80%, 6.9% and 1.2% of children respectively. At 6 months the proportion of children with anaemia decreased to 46% (p<0.001) and 32% (p<0.001) at 12 months after cART; and thrombocytopaenia decreased to 1.9% (p<0.320) and 0.86% (p=0.017). Conclusions: The majority of HIV-infected patients are anaemic at baseline. This study shows that at 6 and 12 months, there is significant reduction in anaemia and thrombocytopaenia, likely related to cART.
Research report is submitted in partial fulfillment of the requirements for the degree of Master of Medicine in the Department of Pediatrics and Child Health, Faculty of Health Sciences, University of the Witwatersrand, Johannesburg. May 2016